Kinerja Perusahaan Umum Daerah Air Minum dalam Memberikan Pelayanan di Kecamatan Alak Kota Kupang - Inri Maria Tanesib; Yohanes Tuan; Norani Asnawi (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The existence of the Regional Public Company (PERUMDA) of Kupang City aims to distribute water to residents in the surrounding areas. This study aims to evaluate the performance of PERUMDA in providing clean water services in Alak District, Kupang City. This research employs a combination of juridical and empirical approaches. The study was conducted at the PERUMDA Kupang City office and in the Alak District area of Kupang City during January 2025. The population in this study includes all PERUMDA employees and drinking water customers in Alak District, Kupang City. The sample was obtained using purposive sampling techniques, consisting of the head of the customer relations division (1 person), PERUMDA employees (10 people), and community members who use PERUMDA services (50 people), resulting in a total sample of 61 respondents. Data were collected through document review and in-depth interviews guided by an interview protocol. Based on the interview results, it was found that clean water services provided by PERUMDA were still suboptimal. Although PERUMDA Kupang City already has Standard Operating Procedures (SOPs), the implementation in the field still faces various obstacles, such as unequal distribution of clean water, limited infrastructure, occasional poor water quality, ineffective complaint handling systems, and outstanding payment arrears. PERUMDA Kupang City needs to expand its clean water distribution network, improve water quality, strengthen the customer complaint system, and conduct education and outreach to the community regarding the importance of efficient water use and the obligations of the community as service users.